Land use change effects on trace gas fluxes in the forest margins of Central Sulawesi, Indonesia - Veldkamp, E.; Purbopuspito, J.; Corre, M.D.; Brumme, R.; Murdiyarso, Daniel (American Geophysical Union, 2008)
Land use changes and land use intensification are considered important processes contributing to the increasing concentrations of the greenhouse gases nitrous oxide (N2O) and methane (CH4) and of nitric oxide (NO), a precursor of ozone. Studies on the effects of land use changes and land use intensification on soil trace gas emissions were mostly conducted in Latin America and only very few in Asia. Here we present results from Central Sulawesi where profound changes in land use and cultivation practices take place: traditional agricultural practices like shifting cultivation and slash‐and‐burn agriculture are replaced by permanent cultivation systems and introduction of income‐generating cash crops like cacao. Our results showed that N2O emissions were higher from cacao agroforestry (35 ± 10 μg N m−2 h−1) than maize (9 ± 2 μg N m−2 h−1), whereas intermediate rates were observed from secondary forests (25 ± 11 μg N m−2 h−1). NO emissions did not differ among land use systems, ranging from 12 ± 2 μg N m−2 h−1 for cacao agroforestry and secondary forest to 18 ± 2 μg N m−2 h−1 for maize. CH4 uptake was higher for maize (−30 ± 4 μg C m−2 h−1) than cacao agroforestry (−18 ± 2 μg C m−2 h−1) and intermediate rates were measured from secondary forests (−25 ± 4 μg C m−2 h−1). Combining these data with results from other studies in this area, we present chronosequence effects of land use change on trace gas emissions from natural forest, through maize cultivation, to cacao agroforestry (with or without fertilizer). Compared to the original forests, this typical land use change in the study area clearly led to higher N2O emissions and lower CH4 uptake with age of cacao agroforestry systems. We conclude that this common land use sequence in the area combined with the increasing use of fertilizer will strongly increase soil trace gas emissions. We suggest that the future hot spot regions of high N2O (and to a lesser extend NO) emissions in the tropics are those areas where climatic and edaphic conditions allow for intensive agriculture. This scenario is probably preferable over the alternative of agriculture extensification, which would imply a dramatic increase in deforestation rates with accompanying CO2 emissions.